2014
DOI: 10.1021/es405096q
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molecular Structure and Adsorbent Properties on Sorption of Organic Compounds to a Temperature Series of Wood Chars

Abstract: Chars from wildfires and soil amendments (biochars) are strong adsorbents that can impact the fate of organic compounds in soil, yet the effects of solute and adsorbent properties on sorption are poorly understood. We studied sorption of benzene, naphthalene, and 1,4-dinitrobenzene from water to a series of wood chars made anaerobically at different heat treatment temperatures (HTT) from 300 to 700 °C, and to graphite as a nonporous, unfunctionalized reference adsorbent. Peak suppression in the NMR spectrum by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(111 citation statements)
references
References 35 publications
9
99
1
Order By: Relevance
“…Ahmad et al (2013) showed that sorption of trichloroethylene to pine needle biochar was proportional to pyrolysis temperature (300-700°C) due to the large surface area, low polarity, and increased aromaticity. In contrast, Lattao et al (2014) showed that sorption of benzene, naphthalene, and 1,4-dinitrobenzene was maximized at 500°C (among 300-700°C) and that it did not show any typical trends with surface area, micropore and mesopore volumes, or H/C and O/C ratios. In order to determine the effect of pyrolysis temperature on the sorption of the ionizable compounds to biochar, the sorption of DCP and triclosan was investigated using RS biochars synthesized at 250-900°C.…”
Section: Resultsmentioning
confidence: 79%
“…Ahmad et al (2013) showed that sorption of trichloroethylene to pine needle biochar was proportional to pyrolysis temperature (300-700°C) due to the large surface area, low polarity, and increased aromaticity. In contrast, Lattao et al (2014) showed that sorption of benzene, naphthalene, and 1,4-dinitrobenzene was maximized at 500°C (among 300-700°C) and that it did not show any typical trends with surface area, micropore and mesopore volumes, or H/C and O/C ratios. In order to determine the effect of pyrolysis temperature on the sorption of the ionizable compounds to biochar, the sorption of DCP and triclosan was investigated using RS biochars synthesized at 250-900°C.…”
Section: Resultsmentioning
confidence: 79%
“…Better understanding these mechanisms is important as biochar production parameters (e.g., source material, final pyrolysis temperature, heating rate, and duration or surrounding gases) can be manipulated to produce biochars with optimum characteristics (e.g., surface area, pore size distribution, and surface chemistry) for the sorption of a contaminant of concern (Lattao et al, 2014;Sun et al, 2012a;Uchimiya et al, 2011b).…”
Section: Batch Sorption Studies To Elucidate Biochar Sorption Mechanismsmentioning
confidence: 99%
“…Instead, the authors couple the use of 77 K N 2 isotherms with CO 2 sorption isotherms conducted at 273 K to get an accurate measurement of both meso-and microporosity. Lattao et al (2014) used measures of both of these parameters and others likely to affect HOC sorption to biochar in a comprehensive study to better understand the factors controlling sorption. All these parameters on their own failed to predict sorption, although a model relating sorption to a weighted sum of micro-and mesoporosity was more successful.…”
Section: Batch Sorption Studies To Elucidate Biochar Sorption Mechanismsmentioning
confidence: 99%
“…Numerous studies have attempted to explore the relationships between biochar properties and pyrolysis conditions (Sensöz and Angin, 2008;Keiluweit et al, 2012;Zhao et al, 2013). However, by detailed analysis we find that most of these studies only investigate the impacts of one or two production parameters such as temperature (Al-Wabel et al, 2013;Lattao et al, 2014) and temperature plus heating rate (Angin, 2013) on the properties of biochars in order to get proper biochars for carbon sequestration and contaminant adsorption, and that the effect of atmosphere for biochar production was mostly neglected.…”
Section: Introductionmentioning
confidence: 99%